Implementation of physical education with blended learning based on teacher readiness in Indonesia: systematic review - Cahyo Nugroho Sigit; Muhammad Aliffajaruddin Alfani; Wasis Djoko Dwiyogo (Journal of Science and Education (JSE), 2022)
This conceptual article is an overview of the implementation of the blended learning model for physical education learning in the modern era, especially in Indonesia. The data obtained in this conceptual article is secondary data using the google schoolar database using a systematic review approach with PRISMA (Preferred Reporting Items for literature reviews) analysis. Based on the results of the conclusions related to the systematic review that has been carried out, it can be concluded that the synergy between teacher readiness in mastering technology, the role of government through constructive programs, and high student literacy awareness. The combination of fulfilling these roles creates a good combination in the application of blended learning to physical education learning in this modern era.